Keragaman dan Penyebaran Benalu pada Tanaman Koleksi di Kebun Raya Cibodas, Jawa Barat - Uji, Tahan; Sunaryo, Sunaryo (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
A study on mistletoe has been carried out in Cibodas Botanical Garden,West Java. The aim of the study were to know mistletoe diversity which have attacked many collection plants species in the area. Result of the study indicated that there were 5 species mistletoe (i.e. Dendrophthoe pentandra, Scurrula oortiana, Macrosolen cochinchinensis, Lepeostegeres gemmiflorus and Viscum articulatum) and they attacked 91 collection plants species in Cibodas Botanical Garden. D. pentandra was reported as the most abudance mistletoe. Collection plants species of familes Moraceae and Myrtaceae were also reported as the highest of collection plants species have been parasited by mistletoe.